A systematic review of empirical studies on multidisciplinary design collaboration: Findings, methods, and challenges. (July 2022) - Nguyen, Mimi; Mougenot, Céline
Abstract : While multidisciplinary collaboration is increasingly considered as a prerequisite for innovation in design, it is unclear what has been studied and what to investigate next. To address this, we conducted a systematic literature review on multidisciplinary design collaboration, focussing on what has been found, and how these studies have been implemented. Following a PRISMA approach, 17 papers were selected for a critical review. A co-occurrence analysis found that the selected literature covered five themes centred on communication, all highlighting the importance of shared understanding in multidisciplinary design collaboration. Further analysis revealed biases and differences between the methodological approach followed in the studies. For future research, we suggest investigating two under-explored areas of design collaboration: distributed work and digital/service-oriented design activities. Highlights: First systematic review of studies into multidisciplinary design collaboration. We found five thematic clusters all showing the importance of shared understanding. We found a lack of methodological consistency and great variation in the findings. We discuss the limited generalisability and low industrial relevance of these studies. We suggest to study collaboration in 'distributed' work and in 'digital' design.